THE INFLUENCE OF BOARD GAME TOWARDS STUDENTSâ€™ VOCABULARY MASTERY OF THE TENTH CLASS AT SMA NEGERI 2 PADANG CERMIN PESAWARAN IN 2015/2016 - Zwesty, Ermina Deasya (LPPM STKIP PGRI Bandar Lampung, 2016)
Vocabulary is meaningful of words or can be meaning full of sentences. Vocabulary is also something or mentality that owned by human being in its consciousness and the â€œsomethingâ€ is given inherently to name, describe a certain thing or condition. Many students fine difficulty in mastering vocabulary. The problem comes when the students difficult to know the meaning of word and they are getting difficult in memorizing the meaning of words. In this research, the writer used cluster random sampling technique. The sample was two classes and divided into two classes. The first class was experimental class and the second was control class. In collecting the data, the writer used vocabulary test in objectives form. The test consists of 50 items with five options. In analyzing the data the writer used ttest, the formula. After the data was analyzed by using ttest formula, it was got ttest or tratio = 4.99 at significance level 5% = 2.00 and at significance level 1%=2.66. Since tratio>ttable, Ho is rejected and Ha is accepted. It means that there was positive influence of board game towards studentsâ€™ vocabulary mastery